Variation in functional independence in hospitalized elderly related to social and health variables - Kawasaki, Kozue; Diogo, Maria José D’Elboux (Acta Fisiátrica, 2007)
The aging process, non-transmissible chronic diseases and hospitalizations can cause functional decline in the elderly. Objective: to identify the variation in functional capacity in elderly during hospitalization and correlate it with social and health variables. Method: The study was developed at a University Hospital in Campinas, SP, with 28 elderly inpatients of both sexes, admitted for clinical treatment, with a mean age of 68 years. The Functional Independence Measure (FIM) was used at the admission, during the hospitalization, at the discharge and one month after the discharge. The variation in FIM scores was calculated at different moments of evaluation, expressed by deltas and correlated with the variables: gender, previous hospitalization, presence of caregiver and use of medications. Results: There was a significant difference in the deltas of FIM between the discharge-home return periods (p=0.0010) and the admission-discharge periods (p<0.0001), in total FIM and its domains, showing decreased functional independence during hospitalization and recovery after the return home. The gender, previous hospitalization and presence of caregiver did not significantly influence the functional capacity of the elderly inpatients; however the increased number of prescribed medications between the admission and the discharge periods presented a moderate (r=0.5059) and a very significant correlation (p=0.0071) with functional decline in this period. Conclusion: There was a functional decrease in elderly inpatients during the hospitalization, being more significant among inpatients that had an increased number of prescribed medications during hospitalization.